2014
DOI: 10.1186/1471-2334-14-400
|View full text |Cite
|
Sign up to set email alerts
|

Non typable-Haemophilus influenzae biofilm formation and acute otitis media

Abstract: BackgroundNon-typable Haemophilus influenzae (NT-Hi) infection is frequently associated with acute otitis media (AOM) treatment failure, recurrence or chronic otitis media. Persistence of otopathogens in a biofilm-structured community was implicated in these situations. Here, we compared biofilm production by H. influenzae strains obtained by culture of middle ear fluid (MEF) from children with AOM treatment failure and by strains isolated from nasopharyngeal (NP) samples from healthy children or those with AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
1
18
0
2
Order By: Relevance
“…Furthermore, PCV implementation may have led to an additional reduction in prescriptions [ 25 ]. The second hypothesis is more speculative: in our population, most Hi strains now produce biofilms [ 26 ], which allows for resistance to antibiotic treatments without another mechanism of resistance required [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PCV implementation may have led to an additional reduction in prescriptions [ 25 ]. The second hypothesis is more speculative: in our population, most Hi strains now produce biofilms [ 26 ], which allows for resistance to antibiotic treatments without another mechanism of resistance required [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address the ability of the isolates to form biofilms, a semi-quantitative static model which has been demonstrated to be a reliable and reproducible method for assessing biofilm formation in vitro was used. 13 , 14 , 25 Following the advice and approach of others, 25 a number of formulae (3 in total, see materials and methods and Table 1 ) were used on the raw data to offset variations in culture conditions, methodologies and environmental factors. Of the plate count isolates, only the Cupriavidus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm production was evaluated by a modification of the microtiter plate assay with crystal violet (CV) stain as described for NT- Hi [27]. This assay was based on the ability of bacteria to adhere to solid polystyrene surfaces by using biofilm.…”
Section: Methodsmentioning
confidence: 99%
“…Methods based on PCR techniques have been described, but they cannot discriminate between planktonic and biofilm-growing bacteria [26]. In our previous study, by using a modification of the microtiter plate assay with crystal violet (CV) stain, we found that 49% of H. influenzae strains isolated from children’s nasopharynx produced biofilm [27].…”
Section: Introductionmentioning
confidence: 99%